Assessor training strategies and their effects on accuracy, interrater reliability, and discriminant validity - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2001)
This study compares the effects of data-driven assessor training with schema-driven assessor training and control training. The sample consisted of 229 industrial and organizational psychology students and 161 managers who were randomly assigned to 1 of these training strategies. Participants observed and rated candidates in an assessment center exercise. The data-driven and schema-driven assessor training approaches outperformed the control training on all 3 dependent variables. The schema-driven assessor training resulted in the largest values of interrater reliability, dimension differentiation, and accuracy. Managers provided significantly more-accurate ratings than students but distinguished less between the dimensions. Practical implications regarding the design of assessor trainings and the composition of assessor teams are proposed.